Analiza Możliwości Półtrepanacji Wielootworowej w Przypadku Jednoosiowego Stanu Naprężenia - Z. Dyląg; Z. Orłoś (Engineering Transactions, 1960)
The possibility of application of the multi-hole semi-trepanation method to the investigation of one-directional states of stress is analyzed. The analysis is based on strain-gauge tests of stretched plate strips with and photoelastic holes arranged in various ways. For the interpretation of the results the dimensional analysis is used. On the basis of the investigations the following conclusions can be drawn. Depending on the arrangement of the holes positive or negative coefficients sensivity can be obtained. In the latter case the region, in which the measurement is done is unloaded, which is more advantageous, the appearance of plastic strains in this region being excluded. As a result of strain gauge tests hole arrangements showing higher values of the sensitivity coefficients y are indicated. In the case of two unloading holes the measurement results and an appropriate dimensional analysis of the para- meters of the system of strain gauges enabled the determination of the relation between the sensitivity coefficient y and the hole diameter d, the distance between the holes b and the length l of the measurement base. This relation has the form […]. A self-compensating system of strain gauges showing better sensitivity and better compensation system was also used in the investigation. Also photoelastic investigations of stress distribution in plate strips with holes were done, the coefficients of form being determined. In the case of two holes these coefficients are compared with those determined on the basis of the theoretical solution by LING. The results obtained enable practical application of the multi-hole semi-trepanation method.